2004
DOI: 10.1029/2003jc001882
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and prediction of wave‐generated suborbital ripples

Abstract: [1] Experiments in a large-scale wave flume using regular and irregular waves with periods between 4 s and 6 s and heights between 0.2 m and 1.55 m have examined the formation of wave-generated ripples using sediment beds composed of four grain sizes (D 50 = 0.349 mm, 0.329 mm, 0.220 mm, and 0.162 mm) in a water depth of approximately 4 m. Estimates of wave-generated ripple height,h, and wavelength, l, were obtained using zero down-crossing analyses of bed profiles measured by acoustic means along a 4-m transe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 44 publications
3
52
0
Order By: Relevance
“…Therefore, in terms of predicting the dimensions of equilibrium ripples generated by full-scale oscillatory flows, the best data arguably come from controlled full-scale laboratory experiments in which there is a high level of certainty about the flow and sand properties and the equilibrium state of the bed. Such studies include the oscillatory flow tunnel experiments of Lofquist (1978), Ribberink and Al-Salem (1994) and O'Donoghue and Clubb (2001) and the full-scale wave flume experiments conducted by Thorne et al (2002) and Williams et al (2004).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in terms of predicting the dimensions of equilibrium ripples generated by full-scale oscillatory flows, the best data arguably come from controlled full-scale laboratory experiments in which there is a high level of certainty about the flow and sand properties and the equilibrium state of the bed. Such studies include the oscillatory flow tunnel experiments of Lofquist (1978), Ribberink and Al-Salem (1994) and O'Donoghue and Clubb (2001) and the full-scale wave flume experiments conducted by Thorne et al (2002) and Williams et al (2004).…”
Section: Introductionmentioning
confidence: 99%
“…The most comprehensive predictor for current-generated, wavegenerated and combined-flow bedforms was proposed by Soulsby et al (2012). Other widely used bedform predictors were proposed by Haque & Mahmood (1985), Baas (1993), van Rijn (1993, Julien & Klaassen (1995), Raudkivi (1997) and Karim (1999) for unidirectional currents, and by Nielsen (1981), van Rijn (1993), Wiberg & Harris (1994), Malarkey & Davies (2003), Grasmeijer & Kleinhans (2004), Williams et al (2004Williams et al ( , 2005, Camenen & Larson (2006), Yan et al (2008), Camenen (2009), Pedocchi & Garcia (2009) and Nelson et al (2013) for oscillatory currents.…”
Section: Bedforms In Non-cohesive Sedimentmentioning
confidence: 99%
“…The common method requires a prediction of ripple geometry and there is no lack of published empirical relationships from laboratory and field measurements relating ripple dimensions to flow and sediment characteristics (e.g., Miller and Komar 1980, Nielsen 1981, Grant and Madsen 1982, Kos'yan 1988, Wikramanayake and Madsen 1994, Wiberg and Harris 1994, Mogridge et al 1994, Faraci and Foti 2002, Williams et al 2004, O'Donoghue et al 2006. Each formula performs well against the data used in its formulation, as expected, but generally much less successfully under reasonably different conditions.…”
Section: Common Methodsmentioning
confidence: 78%
“…It is physically reasonable to expect the larger waves in a random wave train to have a greater effect on the ripple dimensions than the smaller waves, which suggests that a near-bottom velocity greater than the rms velocity is necessary to represent random waves. Faraci and Foti (2002) and Williams et al (2004) similarly found that a single relationship could be used to represent ripple geometry under both types of waves if the significant wave height was used for the random waves. Furthermore, representing random waves with the significant near-bottom velocity has been used to successfully consolidate data in other boundary layer processes, such as initiation of motion (Madsen 2002).…”
Section: Common Methodsmentioning
confidence: 99%